The Political and Economic Conditions to Abadan City during Abbasid Era - Al Khalidi, Ragheed Gummar Majeed; Al Jubouri, Khaleda Hamood Salman (Al-Adab Journal, 2019)
The city of Abadan is considered one of the important cities in the Arab Islamic state. It is located on village that is collected the Euphrates and Tigris rivers , rather than represented an important port during Abbasid era. In addition to Abadan city that had witnessed many of political events and wars , the economic activity illustrates the people works in the agricultural , industrial , and traditional fields.